1999
DOI: 10.1021/ma990045o
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of Carbon Monoxide with Ethene Catalyzed by Palladium(II) Complexes of 1,3-Bis(diphenylphosphino)propane Ligands Bearing Different Substituents on the Carbon Backbone

Abstract: In this work are described the syntheses of several new dppp-like ligands (dppp =1,3-bis(diphenylphosphino)propane) bearing different substituents on the carbon backbone and of their palladium(II) complexes with acetate or trifluoroacetate coligands (L). The complexes exhibit the general formula Pd(P−P)(L)2 and have been employed as catalyst precursors for the copolymerization of ethene and carbon monoxide in MeOH under experimental conditions that are comparable to those reported in the relevant literature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 40 publications
6
49
0
1
Order By: Relevance
“…For instance, Bianchini et al demonstrated that the introduction of alkyl groups in the 2-position of the carbon backbone of dppp does not improve the catalytic activity of the corresponding palladium (II) precursors. [28] By contrast, a considerable increase of the productivity (i.e., more than 50%) was obtained when alkyl groups were introduced in both 1-and 3-position of the dppp backbone, to yield both the meso-2,4-bis(diphenylphosphino)pentane (meso-bdpp, 2, Figure 1) and the rac-bdpp. Under comparable experimental conditions, meso-bdpp has been reported to be more active in the palladiumcatalyzed CO/ethylene copolymerization than dppp or racbdpp.…”
Section: Pdmentioning
confidence: 99%
“…For instance, Bianchini et al demonstrated that the introduction of alkyl groups in the 2-position of the carbon backbone of dppp does not improve the catalytic activity of the corresponding palladium (II) precursors. [28] By contrast, a considerable increase of the productivity (i.e., more than 50%) was obtained when alkyl groups were introduced in both 1-and 3-position of the dppp backbone, to yield both the meso-2,4-bis(diphenylphosphino)pentane (meso-bdpp, 2, Figure 1) and the rac-bdpp. Under comparable experimental conditions, meso-bdpp has been reported to be more active in the palladiumcatalyzed CO/ethylene copolymerization than dppp or racbdpp.…”
Section: Pdmentioning
confidence: 99%
“…BH 3 (27) gave the boron-protected bidentate phosphine ligands [23][24][25][26]. [61,62] Deboronation of the phosphines 23-26 was achieved by the addition of an excess of tetrafluoroboric acid to give an in situ prepared phosphonium salt that was then reduced to the desired phosphine by the addition of potassium hydroxide.…”
Section: A C H T U N G T R E N N U N G (O 3 Sch 3 )A C H T U N G T R mentioning
confidence: 99%
“…In the present work the precursor is [PdCl 2 (dppf)], but since it is well known that water is capable of coordinating Pd(II) with the formation of aqua-complexes and also that the monomers are capable to coordinate Pd(II) [41,42], it is plausible to suppose that [PdCl 2 (dppf)] undergoes equilibrium 1 (Scheme 1) [28,43]. Upon increasing the concentration of H 2 O, the formation of a cationic aqua-complex is favored also by the increasing of the dielectric constant of the reaction medium, which favors the separation of the charges.…”
Section: Proposed Catalytic Cyclementioning
confidence: 99%